1975
DOI: 10.3758/bf03333187
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced ulceration in adrenalectomized and normal rats

Abstract: his experiment examined the influence of plasma corticosterone on stress-induced ulceration in restrained rats. Gastric pathology and plasma corticosterone levels were examined in normal (UNOP) and adrenalectomized (ADX) rats under two conditions of shock predictability. The severity of the gastric ulceration in unoperated rats given noncontingent presentations of a tone and an electric shock was greater than in subjects receiving shocks contingent upon CS presentation. When ulcer pathology was evaluated for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Similar results were obtained by Simpson et al (1975), who used a single 19-hr session and tail shock. Adrenalectomized and unoperated rats were given predictable, unpredictable, or no-shock conditions.…”
Section: Stomach Lesionssupporting
confidence: 85%
See 2 more Smart Citations
“…Similar results were obtained by Simpson et al (1975), who used a single 19-hr session and tail shock. Adrenalectomized and unoperated rats were given predictable, unpredictable, or no-shock conditions.…”
Section: Stomach Lesionssupporting
confidence: 85%
“…We mentioned 'that differential food consumption may affect ulceration. Still, when differential food consumption is not present, predictable shock again results in less ulcer development (Caul et al, 1972;Guile & McCutcheon, in press;Mezinskis et al, 1971;Price, 1972;Simpson et al, 1975;Weiss, 1970). Fare's (1964 study is the only long-term investigation that examined differential ulceration due to predictable and truly unpredictable shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suggestions that REM may be important for emotional processing also may appear to be at odds with the prevailing view that predictable shock is less anxiogenic than unpredictable shock, based on findings that animals prefer signaled over unsignaled shocks. [11][12][13] However, studies have also reported that predictable shock is associated with an increase in ulcer development, 34,35 greater weight loss, 36,37 and increased susceptibility to disease. 38 Indeed, the preference for predictability is likely affected by several experimental parameters, including shock intensity, signal duration, inter-shock intervals, amount of training, and the dependability of shock-free periods.…”
Section: Predictive Cues and Learningmentioning
confidence: 99%
“…On the other hand, Simpson, Wilson, DiCara, Jarrett, and Carroll (1975) failed to find any differences between predictable and unpredictable groups, as did Hennessy, King, McClure, and Levine (1977) and Davis and Levine (1982). The only study to demonstrate a greater elevation in corticosterone values in the unpredictable group is that of Weiss (1970).…”
Section: Discussionmentioning
confidence: 76%